Highly active and selective AlSBA-15 catalysts for the vapor phase tert-butylation of phenol - Vinu, A.; Devassy, Biju M.; Halligudi, Shivaraj B.; Bohlmann, W.; Hartmann, Martin (Applied Catalysis A-General, 2005)
Hexagonally ordered mesoporous AISBA-15 catalysts having n(Si)/(nA]) ratios from 7 to 215 have been synthesized hydrothermally using a cheap non-ionic block copolymer as the structure-directing agent. The obtained materials were analyzed by XRD and nitrogen adsorption to determine the structural order and the textural properties. It has been observed by Al-27 MAS NMR spectroscopy that aluminum atoms are exclusively in tetrahedral coordination for all samples except AISBA-15(7), where octahedral aluminum has been detected to some extent. Temperature-programmed desorption of pyridine showed that AISBA-15(45) has a higher number of strong acid sites as compared to other mesoporous materials such as FeMCM-41, AIMCM-41 and FcAlMCM-41. The catalyst AlSBA-15(45)showed superior performance in the acid-catalyzed tertiary butylation of phenol employing tert-butanol as the alkylation agent. A high phenol conversion of 86.3% is observed for this catalyst at a reaction temperature of 150 degrees C. Over AISBA-15(45), the 4-TBP yield amounts to 40.5% and the 2,4-DTBP yield corresponds to 37.9%. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Acidity; AlSBA-15; aluminum incorporation; butylation of phenol; SBA-15

Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Butylation of toluene: influence of zeolite structure and acidity on 4-tert-butyltoluene selectivity - Pai, Shivanand; Gupta, Upendranath; Chilukuri, Satyanarayana V. (Journal of Molecular Catalysis A-Chemical, 2007)
Vapour phase alkylation of toluene with tert-butyl alcohol was studied over the large pore zeolites H beta, HY and HMCM-22. The influence of the acidity, reaction temperature, run duration, feed rate (WHSV) and molar ratio of the reactants on conversion of toluene and selectivity for 4-tertbutyl toluene was studied. Among the isomers formed during the reaction, the para-isomer was the predominant one, followed by the meta-isomer, while no ortho-isomer was found in the products due to steric factors. 4-tert-Butyl toluene selectivity decreases at higher temperatures, while going through a maximum in the 413-433 K temperature range. Zeolite HY with a high silica to alumina ratio (SiO2/Al2O3 = 80), that has strong acidity, but lower acid site density, possesses high activity for toluene conversion, high alkylation selectivity and also high para-selectivity. The improved para-selectivity of high silica HY zeolite is attributed to the low isomerization activity that results in the suppression of the secondary isomerization of 4-tert-butyl toluene. Both alkylation and selectivity are higher with feed mixtures containing a lower fraction of tert-butyl alcohol. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 4-t-butyltoluene; Acidity; butylation; large pore zeolites; Toluene

Dehydration of fructose to 5-hydroxymethyl furfural over ordered AlSBA-15 catalysts - Lucas, Nishita; Kokate, Ganesh; Nagpure, Atul; Chilukuri, Satyanarayana V. (Microporous and Mesoporous Materials, 2013)
5-Hydroxymethyl furfural is an important platform chemical. It is successfully synthesized from renewable carbohydrates using mesoporous AlSBA-15 catalysts under biphasic conditions. Fine tuning of the catalyst acidity is important to drive the reaction to give good yields of furan compound. Al-SBA-15 catalysts with different Si/Al ratios were prepared and characterized by XRD, Al-27 MASNMR, SEM, TEM, N-2 sorption, ICP-OES and TPD of ammonia. Results show that part of aluminium is substituted into tetrahedral positions. The catalyst with lower acid site density but medium to strong acid strength favours selective formation of HMF. Under the optimized conditions, HMF selectivity was as high as 88% at 59 mol% conversion of fructose. Leaching of part of aluminium occurs under hydrothermal conditions, if solvent mixtures containing water are used, while activity can be retained if DMSO is used as solvent. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acidity; AlSBA-15; dehydration; fructose; Hydroxymethyl furfural

Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Highly efficient micro-meso acidic H-USY catalyst for one step conversion of wheat straw to ethyl levulinate (biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Mudliar, Sandeep; Bokade, Vijay (Microporous and Mesoporous Materials, 2020)
Ethyl Levulinate (EL), biofuel additive can blend up to 20% with biodiesel to improve its fuel properties. Till the date, there are reports on homogeneous catalysts (H2SO4, ionic liquid) for synthesis of EL from raw biomass like wheat straw. To best of our knowledge, there is no single report on heterogeneous catalyst for one step synthesis of EL directly from wheat straw. This work is a successful attempt to use heterogeneous micro-meso acidic H-USY (post dealumination and desilication) for direct one step conversion of wheat straw to EL with higher EL yield 24.5 wt%, which is probably the highest so far.
Keywords: Acidity; ethyl levulinate; H-USY; Micro-meso; Wheat straw

Supported MoOx and WOx solid acids for biomass valorization: interplay of coordination chemistry, acidity, and catalysis - Sudarsanam, Putla; Gupta, Navneet Kumar; Mallesham, Baithy; Singh, Nittan; Kalbande, Pavan Narayan; Reddy, Benjaram M.; Sels, Bert F. (ACS Catalysis, 2021)
Supported molybdenum oxide (MoOx) and tungsten oxide (WOx) materials are a vital class of solid acid catalysts for the chemical industry because of their nontoxic nature, strong acidity, remarkable stability in water, hydrogen, and oxygen atmospheres, and excellent reusability performance. These fascinating solid acids play a pivotal role in developing sustainable catalytic routes for renewable biomass processing to produce value-added fuels, chemicals, and platform molecules. The coordination chemistry of MoOx and WOx on the support materials (oxides, carbons, or zeolites) controls their acidic strength, active site accessibility, and catalytic activity. Hence, significant efforts have been made toward optimizing the conditions used for catalyst synthesis and biomass processing to tune the coordination chemistry of MoOx and WOx with the substrate molecules and, thus, their acid-activity/selectivity performance. This Review provides a comprehensive overview of supported MoOx and WOx solid acids for biomass valorization. The importance of the biomass and the role of solid acids for biomass valorization were emphasized, followed by a brief discussion of supported MoOx and WO(x )solid acids. Afterward, the interplay of coordination chemistry, acidic strength, and catalytic activity of supported MoOx and WOx solid acids was discussed. Finally, their catalytic applications for the valorization of several biomass substrates and their derivatives were summarized. This Review will provide valuable insights for developing advanced supported WOx and MoOx solid acids for catalytic biomass valorization and other challenging acid-catalyzed processes.
Keywords: Acidity; biomass valorization; catalysis; Coordination chemistry; molybdenum oxide; tungsten oxide

Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw